2011
DOI: 10.1177/1362361309356929
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of complex motor dysfunction in drug naïve children with autism using automatic motion analysis of gait

Abstract: In order to increase the knowledge of locomotor disturbances in children with autism, and of the mechanism underlying them, the objective of this exploratory study was to reliably and quantitatively evaluate linear gait parameters (spatio-temporal and kinematic parameters), upper body kinematic parameters, walk orientation and smoothness using an automatic motion analyser (ELITE systems) in drug naïve children with Autistic Disorder (AD) and healthy controls. The children with AD showed a stiffer gait in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 39 publications
11
69
0
1
Order By: Relevance
“…The magnitude of these kinematic atypicalities was significantly positively correlated with autism symptom severity as measured by the Autism Diagnostic Observation Schedule semi-structured questionnaire [116]. Such results are consistent with reports from other laboratories of atypically jerky arm [47] and whole-body [36] movements in autism. In a separate perception task, participants watched a series of visual stimuli comprising an image of a human hand that made vertical sinusoidal movements (down and then up) across the computer screen.…”
Section: (A) Movement Similarity and Action Perception In Autismsupporting
confidence: 89%
See 1 more Smart Citation
“…The magnitude of these kinematic atypicalities was significantly positively correlated with autism symptom severity as measured by the Autism Diagnostic Observation Schedule semi-structured questionnaire [116]. Such results are consistent with reports from other laboratories of atypically jerky arm [47] and whole-body [36] movements in autism. In a separate perception task, participants watched a series of visual stimuli comprising an image of a human hand that made vertical sinusoidal movements (down and then up) across the computer screen.…”
Section: (A) Movement Similarity and Action Perception In Autismsupporting
confidence: 89%
“…At least seven separate studies have assessed gait or the 'style of walking' in autistic children and adults, and a number of atypicalities have been observed [33][34][35][36][37]. For example, Nobile et al showed that, compared with typical individuals, autistic children (6-14 years) exhibited trunk postural abnormalities, difficulties in walking in a straight line, a marked loss of smoothness (an increase in the jerkiness of movement) and, in general, a stiffer gait in which the usual fluidity of walking was lost.…”
Section: (C) Gaitmentioning
confidence: 99%
“…A very recent study by Nobile et al used a novel automatic motion analyzer to characterize gait in children with ASD and typical controls. They found that children with ASD exhibited a stiffer gait with lack of “smoothness,” struggled to maintain a straight line, and showed evidence of poor postural control [20]. A strength of this investigation was the use of a quantitative, automated system to characterize a motor domain that can be challenging to objectively measure.…”
Section: Motor Disturbancementioning
confidence: 99%
“…In the present study, integrated jerk was calculated as the area under the curve of the Euclidean jerk vector obtained from the three linear axes. Following previous research that has studied the jerk of voluntary movements in clinical populations, the integrated jerk for each trial was normalised for both movement extent and movement duration before undergoing analysis (Hogan & Sternad, 2009;Nobile et al, 2011;Romero, Van Gemmert, Adler, Bekkering, & Stelmach, 2003;Teulings, Contreras-Vidal, Stelmach, & Adler, 1997).…”
Section: Illusion Ratingsmentioning
confidence: 99%